2013
DOI: 10.1016/j.molcel.2013.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Telomeric Noncoding RNA TERRA Is Induced by Telomere Shortening to Nucleate Telomerase Molecules at Short Telomeres

Abstract: Elongation of a short telomere depends on the action of multiple telomerase molecules, which are visible as telomerase RNA foci or clusters associated with telomeres in yeast and mammalian cells. How several telomerase molecules act on a single short telomere is unknown. Herein, we report that the telomeric noncoding RNA TERRA is involved in the nucleation of telomerase molecules into clusters prior to their recruitment at a short telomere. We find that telomere shortening induces TERRA expression, leading to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
198
3
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 204 publications
(234 citation statements)
references
References 38 publications
19
198
3
6
Order By: Relevance
“…However, single-telomere TERRA transcripts only transiently localize with telomeres, which is consistent with previous studies showing that only a small fraction of total TERRA transcripts co-localize with telomeres in fixed or living cells [5,17]. A transient localization of single-telomere TERRA molecules at chromosome ends was also previously observed in yeast by live-cell imaging, indicating that this is a conserved feature of TERRA transcripts [13]. By performing single particle tracking analyses, we observed that the diffusion coefficients of TERRA clusters overlap with the diffusion coefficients of telomeres.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…However, single-telomere TERRA transcripts only transiently localize with telomeres, which is consistent with previous studies showing that only a small fraction of total TERRA transcripts co-localize with telomeres in fixed or living cells [5,17]. A transient localization of single-telomere TERRA molecules at chromosome ends was also previously observed in yeast by live-cell imaging, indicating that this is a conserved feature of TERRA transcripts [13]. By performing single particle tracking analyses, we observed that the diffusion coefficients of TERRA clusters overlap with the diffusion coefficients of telomeres.…”
Section: Discussionsupporting
confidence: 90%
“…Considering their sizes and kinetics, larger TERRA foci could represent clusters of TERRA transcripts which may be bound to chromatin or assembled in large ribonucleoprotein particles (RBPs). Interestingly, similar TERRA clusters have been observed in budding yeast [13], suggesting that the capacity of this lncRNA to form high-ordered structures may be conserved among eukaryotes.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations